Nuevo registro de sinantropía de Filistatoides insignis (Araneae: Filistatidae) en México y actualización del listado de arañas actuales de Chiapas - García-Villafuerte, Miguel Angel; Brescovit, Antonio Domingos (Instituto de Ecología, A.C., 2019)
With the discovery of Filistatoides insignis (O. Pickard-Cambridge, 1896), a new record of synanthropic spider from Mexico, this work aims to update the list of the extant spiders from Chiapas. The specimens were collected at the Museum of Paleontology “Eliseo Palacios Aguilera”, located at Tuxtla Gutiérrez city. With 533 species, Chiapas houses 22.2 % of the biodiversity of spiders recorded from Mexico, occupying the first place on the spider’s richnnes for the country.